2016
DOI: 10.1037/apl0000140
|View full text |Cite
|
Sign up to set email alerts
|

Who strikes back? A daily investigation of when and why incivility begets incivility.

Abstract: Incivility at work-low intensity deviant behaviors with an ambiguous intent to harm-has been on the rise, yielding negative consequences for employees' well-being and companies' bottom-lines. Although examinations of incivility have gained momentum in organizational research, theory and empirical tests involving dynamic, within-person processes associated with this negative interpersonal behavior are limited. Drawing from ego depletion theory, we test how experiencing incivility precipitates instigating incivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
301
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 250 publications
(345 citation statements)
references
References 99 publications
21
301
3
Order By: Relevance
“…These results provide support for the allegation that self‐blame can potentially allow targets to perceive self‐responsibility for improving their predicament (Janoff‐Bulman, ), and when coupled with high emotional control can galvanize employees into reacting in a prosocial manner toward their coworkers. Importantly, our findings extend prior research that has generally portrayed targets of workplace incivility as passive recipients of mistreatment who eventually succumb to emotional distress (Schilpzand, Leavitt, & Lim, ) or engage in withdrawal behavior or hostile responses such as retaliating or behaving in an uncivil manner to innocent others (Foulk et al, ; Gallus et al, ; Rosen et al, ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results provide support for the allegation that self‐blame can potentially allow targets to perceive self‐responsibility for improving their predicament (Janoff‐Bulman, ), and when coupled with high emotional control can galvanize employees into reacting in a prosocial manner toward their coworkers. Importantly, our findings extend prior research that has generally portrayed targets of workplace incivility as passive recipients of mistreatment who eventually succumb to emotional distress (Schilpzand, Leavitt, & Lim, ) or engage in withdrawal behavior or hostile responses such as retaliating or behaving in an uncivil manner to innocent others (Foulk et al, ; Gallus et al, ; Rosen et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…Despite its low intensity, workplace incivility has high incidence in the workplace, with as much as 71% of employees reporting to have experienced uncivil behaviors at work within a 5‐year period (Cortina, Magley, Williams, & Langhout, ). Research commonly associated the experience of workplace incivility with both psychological and behavioral detriments for the targets, such as the experience of greater anxiety and depression (Lim, Cortina, & Magley, ), and the exhibition of similar ill‐mannered behaviors (Foulk, Woolum, & Erez, ; Gallus, Bunk, Matthews, Barnes‐Farrell, & Magley, ; Rosen, Koopman, Gabriel, & Johnson, ) or withdrawal behaviors (Schilpzand, Leavitt, & Lim, ; Sliter, Sliter, & Jex, ). These findings reinforced incivility as a highly unfavorable relational phenomenon in the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we also contribute to the small but growing body of research that has identified maladaptive outcomes for high CL. Although most studies have found that fostering a high CL results in better outcomes like lower incivility (Rosen et al, ), higher organizational learning (Reyt & Wiesenfeld, ), and better joint negotiation outcomes (Henderson & Trope, ), this study shows that in the context of waiting, a high CL may result in more aggressive tendencies.…”
Section: Discussioncontrasting
confidence: 56%
“…The parametric bootstrap uses parameter estimates and standard errors from the analyses to estimate a sampling distribution for the indirect effects and create 95% bias‐corrected confidence intervals (e.g., Selig & Preacher, ). This approach has been used to estimate multilevel mediation in several recently published manuscripts (Lanaj et al., ; Rosen, Koopman, Gabriel, & Johnson, ). We allowed the disturbances between our dependent variables to covary (Kline, ); however, their elimination does not change our results.…”
Section: Resultsmentioning
confidence: 99%